Етнічний фактор у процесі забезпечення національної стабільності - Гудима, Юлія; Керцоя, Тетяна (Видавництво Національного університету "Львівська політехніка", 2009)
In the given article the authors retrace the role of an ethnic factor in the security of the national stability in Ukraine. The notion of ethno-national factor is observed like craving of ethnos to realize their interests in society. In this way the majority of the ethnic communities take active part in the processes of the state creation, they help to create an active interethnic consolidation and the guarantee of the national stability.
Keywords: ethnic factor; national stability